PROSES REKRUTMEN DOSEN PADA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS YAPIS PAPUA - , ELVIRA M. USULU ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine how the implementation of the recruitment process and the factors that affect the recruitment of lecturers in the Faculty of Social and Political Sciences, University of Papua Yapis. To analyze the recruitment process, this study used a descriptive research method with a qualitative approach. Techniques of data collection through interviews, and documentation. Data analysis was performed through an interactive process that starts from the process of data collection, data reduction, data display, and conclusion. Based on the results of this study concluded that the process of recruitment of lecturers in the Faculty of Social and Political Sciences, University of Papua Yapis include: 1) the planning and approval of acceptance based on the needs of each program of study